Anthropometric and body composition profile of young professional soccer players - Bernal-Orozco, M. F.; Posada-Falomir, M.; Quiñónez-Gastélum, C. M.; Plascencia-Aguilera, L. P.; Arana-Nuño, J. R.; Badillo-Camacho, N.; Márquez-Sandoval, F.; Holway, F. E.; Vizmanos-Lamotte, B. (The Journal of Strength and Conditioning Research, 2020)
The purpose was to describe the anthropometric and body composition profile of young professional soccer players and to compare the players profiles between different competitive divisions and playing positions. A retrospective cross-sectional study was carried out with anthropometric data obtained from the records of soccer players of Club Deportivo Guadalajara, S.A. de C.V. (Mexico) in the under-17, under-20, second, third, and fourth division categories. Body mass, height, sitting-height, skinfolds, girths, and bone breadths were measured by certified anthropometrists from September 2011 to March 2015, following the procedures recommended by the International Society for the Advancement of Kinanthropometry. Body composition was determined using the 5-way fractionation method. Comparisons between playing positions in each division and between divisions were performed using analysis of variance, and Bonferroni's post-hoc analyses (SPSS version 22 for Windows, p < 0.05 considered as significant). Data from 755 subjects were analyzed. The mean age was 18.1 ± 1.7 years old (minimum 14.8, maximum 23.2). The under-20 division registered higher anthropometric and body composition values than all other competitive divisions. In addition, goalkeepers were taller, heavier, and obtained the highest values for adipose mass, whereas forwards presented higher percentages of muscle mass. These tables can be used during nutritional assessment and nutritional monitoring of players to establish body composition goals. In addition, the strength and conditioning practitioner may also use these data to design effective and specific training programs most suitable to the anthropometric and body composition profile of each player, taking into consideration his competitive division and playing position.